(3eQTO GdeMJGQ Edi NUGFU GdeNJGQs - (3eMeO Hf Ydj Hf CMeO Hf Ydj Hf NeGQhjg Hf Whdhf GdOeTbqj GdUGdMj GdMfaj, TeS GdOjf , J (B953 (3g` s
(3ChdgG (B:s
(3hHYO agPG JYdjb SejJg eQTO GdeMJGQ Edi NUGFU GdeNJGQ dNUJ ajg s
(3BNQgG (B:s
(3aj HYV GdcJH Cf hdO GdRfG dG jONd GdLfg s
(3fSNI KGdKIs
(3hbO dNU ajg GdeDda cJGH CfehPL GddHjH aj NUGFU GdMHjH ddSjhWjs
(3hcJGH GddaX GdecQe HNUGFU GdfHj Udi Gddg Ydjg hSde GdNjVQis
(3hcJGH GdCYdGe HNUGFU Ydjg GdSdGe ddHdbjfj s
(3hcJGH ZGjI GdShd aj faGFS GdQShd ddedbf s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdMOjK h GdeUWdMs